Finite element modeling of FRP-confined concrete using modified concrete damaged plasticity - Hany, Najwa F.; Hantouche, Elie G.; Harajli, Mohamed H. (Engineering structures, 2016)
•FRP-wrapped concrete columns are modeled in ABAQUS under axial compressive loading.•Concrete damaged plasticity model (CDPM) is used to define the concrete properties.•The sensitivity of the column response to the input concrete parameters is studied.•New dilation angle expression and hardening/softening rule are generated.•The finite element results are compared with available experimental results. Finite element (FE) modeling of confined concrete columns is a challenging task because it requires accurate definition of the concrete material model to represent the volumetric behavior of concrete subject to triaxial stress states. When concrete is confined by fiber-reinforced polymer (FRP) composites, the problem becomes more complex due to the passive nature of the FRP confinement. Concrete Damaged Plasticity Model (CDPM) available in the finite element software package (ABAQUS) has been widely used to model reinforced concrete columns under axial stress. However, the use of CDPM has limitations when applied to confined concrete. This paper addresses these limitations and presents a modified Concrete Damaged Plasticity Model. A new set of strain hardening/softening constitutive relationships for both actively confined concrete and FRP-confined concrete are generated and a concrete dilation model is developed. The dilation model is expressed as a function of the stiffness of the FRP-jacket. The modified CDPM is applicable to columns with different types of cross-sections, including circular, square and rectangular and large range of concrete strengths varying from normal to high strength. Finite Element results obtained using the developed modified CDPM showed a very good agreement with test data for FRP confined concrete columns reported in the technical literature.